Strategi Pemasaran Parfum Aroma XXI dalam Meningkatkan Penjualan di Bukittinggi - Asmel Miranti; Jon Kenedi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research is motivated by the growing demand for perfume both in terms of quality and type, of course the right strategy is needed so that businesses can survive amidst competition from similar businesses. The purpose of this research is to analyze the marketing strategies that have been implemented by XXI Aroma perfume to increase sales in the past and formulate marketing strategies that will be implemented by XXI Aroma Perfume in the future. The type of research used by researchers is descriptive qualitative research with using observation, interview and document data collection techniques. The informant in the research was the owner of the Aroma XXI perfume business using the SWOT matrix. The results of this research state that the marketing strategy for aroma perfumes to increase sales is to maintain strength and opportunities to increase product sales in Aroma XXI perfumes so that they can progress and develop. The strengths and opportunities are providing attractive product packaging so that consumers are interested in the products we sell, Providing long-lasting perfume fragrances so that consumers are satisfied with our products, Providing good quality to maintain the loyalty of old customers, Maintaining the quality of the product ingredients used, Improving online marketing so that consumers can easily buy perfume products.